2018
DOI: 10.1371/journal.pbio.2004880
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-mediated m6A modification is required for cerebellar development

Abstract: N6-methyladenosine (m6A) RNA methylation is the most abundant modification on mRNAs and plays important roles in various biological processes. The formation of m6A is catalyzed by a methyltransferase complex including methyltransferase-like 3 (METTL3) as a key factor. However, the in vivo functions of METTL3 and m6A modification in mammalian development remain unclear. Here, we show that specific inactivation of Mettl3 in mouse nervous system causes severe developmental defects in the brain. Mettl3 conditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
197
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(205 citation statements)
references
References 80 publications
7
197
1
Order By: Relevance
“…of the exon skipping events were validated by RT-qPCR, with ~20-40% reduction in exon skipping 25 in the Fmr1 KO relative to WT ( Figure 7B). These skipped exons have previously been found to be associated with defects in brain development and disease pathology (An and Grabowski, 2007; 1 Fugier et al, 2011;Rockenstein et al, 1995;Wang et al, 2018). Figure 7C shows all the RNA 2 processing events that undergo changes in Fmr1-deficient hippocampus relative to WT (p-3 value<0.05, |deltaPSI| ≥ 5%).…”
mentioning
confidence: 79%
“…of the exon skipping events were validated by RT-qPCR, with ~20-40% reduction in exon skipping 25 in the Fmr1 KO relative to WT ( Figure 7B). These skipped exons have previously been found to be associated with defects in brain development and disease pathology (An and Grabowski, 2007; 1 Fugier et al, 2011;Rockenstein et al, 1995;Wang et al, 2018). Figure 7C shows all the RNA 2 processing events that undergo changes in Fmr1-deficient hippocampus relative to WT (p-3 value<0.05, |deltaPSI| ≥ 5%).…”
mentioning
confidence: 79%
“…Because several recent studies examined the relationship of mammalian FMRP as an m 6 A binding protein (Arguello et al, 2017;Edupuganti et al, 2017), and subsequently as an m 6 A effector (Edens et al, 2019;Hsu et al, 2019;Zhang et al, 2018a), we tested further if we could relate Drosophila FMR1 to m 6 A. In our tests, FMR1 was actually mildly depleted from m 6 A probe relative to the A probe ( Figure 1C-D), although peptide counts were similar in both cases ( Supplementary Table 1).…”
Section: Ythdc and Ythdf Are The Dominant Drosophila M 6 A-binding Prmentioning
confidence: 90%
“…Second, many studies have revealed sensitivity of the mammalian nervous system to manipulation of m 6 A factors (Du et al, 2019;Widagdo and Anggono, 2018). Mutants in writer (mettl3 and mettl14), reader (primarily ythdf1), and eraser (FTO) factors have collectively been shown to exhibit aberrant neurogenesis and/or differentiation (Wang et al, 2018a;Yoon et al, 2017) Ma et al, 2018;Wang et al, 2018b;Weng et al, 2018), which impact neural function and organismal behavior (Hess et al, 2013;Koranda et al, 2018;Widagdo et al, 2016). Overall, these observations may be taken as indications for the general usage of m 6 A to guide cell fate transitions along cell lineages, but may also reflect some heightened requirements in neurons, perhaps owing to their unique architectures or regulatory needs (Du et al, 2019;Livneh et al, 2019;Widagdo and Anggono, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The m6A RNA modification is the most plentiful internal modification of mRNA and noncoding RNA in the majority of eukaryotes, as well as appreciably clusters around the stop codon and 3 ′ untranslated region (3′UTR) [7][8][9]. The physiological importance of m6A RNA modification has been confirmed by its pivotal roles in tissue development and differentiation [10][11][12][13][14][15][16]. m6A RNA modification regulates mRNA at different levels, such as structure, maturation, stability, splicing, export, translation, and decay [17].…”
Section: Introductionmentioning
confidence: 99%